The Role of Family Education in the Development of Character According to Ki Hajar Dewantara - Afifah; Herman Nirwana; Dina Sukma (Manajia: Journal of Education and Management, 2025)
For his achievements in politics and education, Ki Hajar Dewantara is also known as a figure who came up with important ideas in Indonesian national education. Through the concept of "Tamansiswa", he promoted education based on Indonesian cultural and national values. His ideas about education are not only focused on the academic aspect, but also on the character and moral formation of students. Ki Hajar Dewantara encouraged that education should not only be done in schools, but also involve the role of the family. He emphasized the importance of the family as the first environment in shaping children's character. Ethical education became an integral part of his educational vision, where values such as manners, honesty, and respect for others were instilled early on. Establish the purpose of Ki Hadjar Dewantara's life journey and contribution to Indonesian national education. The research method used is the literature method, in which information is collected from various literature sources such as books, scientific reports, and journal articles. Literature research is used to gather relevant information from various sources to support the Influence of Family Education and the Growth of Budi Pekerti According to Ki Hajar Dewantara. . According to Ki Hadjar Dewantara, ethical education is not only about teaching theories of good and bad, but more about the daily practice of good behavior. His concept of education encompasses the five main principles in Pancadarma, which include independence, nationality, humanity, culture and nature. This approach aims to build a strong character, in accordance with Indonesian religious and cultural values.